On the transmission of Greek philosophy to medieval Muslim philosophers - Ali, Ishraq (HTS teologiese studies, 2022)
There are two dominant approaches towards understanding medieval Muslim philosophy: (1) Greek ancestry approach and (2) religiopolitical context approach. In the Greek ancestry approach, medieval Muslim philosophy is interpreted in terms of its relation to classical Greek philosophy, particularly to the philosophy of Plato and Aristotle. The religiopolitical context approach, however, views a thorough understanding of the religious and political situation of that time as the key to the proper understanding of medieval Muslim philosophy. Notwithstanding the immense significance of the two approaches for understanding medieval Muslim philosophy, the question on the reason behind medieval Muslim philosophers’ preference for Plato’s Republic over Aristotle’s Politics in political philosophy is not accurately answered. This preference is usually attributed either to the availability or unavailability of the text or to the suitability or unsuitability of the text for Islamic theological views. However, this article shows that neither the availability or unavailability of text nor its suitability or unsuitability for Islamic religious and theological views can appropriately explain medieval Muslim philosophers’ preference for Plato’s Republic over Aristotle’s Politics in their political thought. This article proposes that the key to understand this preference lies in understanding the transmission of Greek philosophy to medieval Muslim philosophers.Contribution: This study highlights the significance of the thorough understanding of the transmission of Greek philosophy to medieval Muslim world as one of the important approaches towards proper understanding of medieval Muslim philosophy, particularly medieval Muslim political philosophy.